Recent advances of eosinophils and its correlated diseases - Tao, Zhang; Zhu, Hua; Zhang, Jiateng; Huang, Zhiming; Xiang, Ze; Hong, Tu (Frontiers in Public Health, 2022)
Eosinophils are differentiated by bone marrow multipotent progenitor cells and are further released into peripheral blood after maturation. Human eosinophils can exhibit unique multi-leaf nuclear morphology, which are filled with cytoplasmic granules that contain cytotoxicity and immune regulatory proteins. In recent years, many studies focused on the origin, differentiation and development process of eosinophils. It has been discovered that the eosinophils have the regulatory functions of innate and adaptive immunity, and can also function in several diseases, including asthma, chronic obstructive pulmonary diseases, acute respiratory distress syndrome, malignant tumors and so on. Hence, the role and effects of eosinophils in various diseases are emphasized. In this review, we comprehensively summarized the development and differentiation process of eosinophils, the research progress of their related cytokines, diseases and current clinical treatment options, and discussed the potential drug target, aiming to provide a theoretical and practical basis for the clinical prevention and treatment of eosinophil-related diseases, especially respiratory diseases. To conclude, the guiding significance of future disease treatment is proposed based on the recent updated understandings into the cell functions of eosinophils.